THE BAHU LAWEYAN LEGEND IN PHOTOGRAPHIC WORK - Putra, Rahdan Hutama; Handriyotopo, Handriyotopo (Seni Media Rekam ISI Surakarta, 2022)
There is a legend of Bahu Laweyan in Surakarta, which is also found in the 19th-century Serat Witaradya by R.N. Ronggowarsito. Bahu Laweyan is a cursed woman; if she marries, her husband will die mystically soon, and the curse will not be lifted until she has been married seven times. The legend of Bahu Laweyan is a concept of folklore re-actualization to be visualized through a Romanticism-influenced photographic medium. The creative process involves three stages: experimentation, reflection, and formation. The photographic visualization of Bahu Laweyan’s stature or characteristics illustrates a charismatic, charming, extremely elegant, beautiful woman, who has a bright face but also dark shadows and lethal powers. This Romanticism-styled photograph synthesizes folklore values (legend) and modern technology (photography).